Konsumsi Yang-Sakral: Amalan dan Air Doa sebagai Terapi Religius Di Probolinggo - Rojabi Azharghany (JURNAL AT-TURAS, 2020)
The practice of the ritualprayer waterand amalan by asking the kiai which is the belief of the community is constructed as a sacred house that can calm their spirituality from the blazing confusion and problems of life. This study aims to find out how the role of the kiai as religious leaders and social leaders in maintaining the spirituality of the people through water rituals of prayer and practice. This study takes the setting of a kiai in Pesantren Nurul Jadid who has the highest number of students in Probolinggo, East Java. The construction of the community of prayer water and practices are assessed using qualitative methods. Researchers chose non-probability sampling techniques by determining the subject in a purposive and snow ball manner. Collecting data with participant observation and interviewing 1 kiai and 8 communities around pesantren who have special needs for prayer and practice water. The data analysis of this study uses the concept approach of Berger's knowledge sociology. The results of the analysis of community construction in the pesantren indicate their need for supernatural power to solve life's problems. The community identifies this power with the kiai. It is this identity that maintains and maintains the social structure of the relationship between the community and the kiai to the present, as well as being externalized by the kiai in conducting spiritual guidance.Keywords: Kiai, Prayer Water and Amalan, Social Construction